Service Electricity Quality Evaluation – a cluster approach - Andrade, M. A. P.; M. Filomena Teodoro; Rosa, A. (22-nd International Conference of Numerical Analysis and Applied Mathematics, 2024)
This study analyzes service continuity metrics provided by E-REDES over ten years (2014–2023), focusing on medium-voltage connections in mainland Portugal. Key indicators—TIEPI, SAIDI, and SAIFI—were used to assess continuity across three Quality Service Regulation (QSR) zones (Zones A, B, and C), classified by population density and municipal code. Zone A, comprising densely populated areas, showed the highest performance with fewer and shorter interruptions. Zone B showed moderate performance, whereas Zone C exhibited the most prolonged and frequent interruptions, exhibiting a need for infrastructure improvements. The study employed a two-step cluster analysis and a linear model analysis to examine disparities across municipalities, with the Silhouette Coefficient validating cluster quality. The analysis revealed statistically significant variations in energy service performance across different municipal codes, with temporal trends showing improvement in continuity metrics alongside increased investment in network infrastructure.